DEVELOPMENT OF ENHANCED POLYMERIC BLEND MEMBRANE FOR REMOVAL OF CARBON DIOXIDE FROM METHANE - MUSHTAQ, ASIM (2018)
The limited performance of pure glassy and rubbery polymeric membranes for natural gas purification, are due to their intrinsic properties. Optimizing their properties by blending both polymers are expected to address the shortage. The main objective of this study is to synthesize enhance polymer blend membranes (EPBM) using glassy polysulfone (PSU) and rubbery polyvinyl acetate (PVAc) with the addition of amines for carbon dioxide (CO2) removal from methane (CH4). The EPBM were developed by varying the composition of PVAc ranging from 5 to 20 wt. % with 95 to 80 wt. % base PSU in dimethylacetamide (DMAc) solvent.